Systematic analysis of button batteries', euro coins', and disk magnets' radiographic characteristics and the implications for the differential diagnosis of round radiopaque foreign bodies in the esophagus. (May 2020) - Meyer, Till Jasper; Grunz, Jan-Peter; Taeger, Johannes; Rak, Kristen; Hagen, Rudolf; Hackenberg, Stephan; Völker, Johannes; Scherzad, Agmal
Abstract: Objectives: Button battery (BB) ingestion can cause life-threatening complications such as esophageal perforation, and mediastinitis. Chest radiography is the method of choice to diagnose BB ingestion. Therefore, an adequate interpretation of X-ray imaging by physicians is mandatory. The study aimed to analyze relevant diagnostic aspects of BB X-ray imaging, and retrospective analysis of the imaging of radiopaque foreign bodies. Methods: All commercially available BBs and different foreign bodies such as euro coins (EC) and disk magnets (DM) were listed according to their sizes and compositions. Furthermore, an X-ray analysis of a test set of BBs, ECs and DMs was performed at angles of 0°, 45°, and 90°. Retrospective assessment of radiological characteristics was performed for patients with a round and radiopaque foreign body in the esophagus Results: Only BBs with a diameter of at least 20 mm had a reliable positive double rim sign at scan angles of 90°, and 45°. The step-off effect was visible in all BBs regardless of the diameter. DMs and ECs presented a homogeneous X-ray weakening at all investigated scan angles. In the retrospective analysis all five cases of BB ingestion showed a double rim sign, all fifteen cases of coin ingestion a homogeneous X-ray weakening. A corrugated margin was detected for 10 cent, 20 cent and 50 cent coins. Conclusions: BBs with a diameter of at least 20 mm showed, depending on the battery model, a more or less pronounced double rim sign and step-off effect in conventional X-ray imaging. However the double rim sign can be simulated by for example a pot magnet. Key points: Chest X-ray is the method of choice to detect button battery ingestion in the esophagus. Halo and double rim signs are only for foreign bodies with a diameter of at least 20 mm the most important radiological characteristics. Pot magnets can simulate a double rim sign. A furrowed margin sign could help to detect 10 cent, 20 cent and 50 cent coins.